Bridging The Gap Between Theory and Practice in Foreign Policy on Myanmar Crisis: Voices from Policymakers - Rifqi Mulya Nauli Siregar; Arry Bainus; Wawan Budi Darmawan (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2025)
Abstract. This research examines the gap between theory and practice in Indonesia's foreign policy toward Myanmar's crisis. Using qualitative methodology through interviews with three informants from Indonesia's Ministry of Foreign Affairs, the study analyzes policymakers' perspectives on the Myanmar situation. Findings of this research showed that Indonesia adopted a pragmatic approach prioritizing operational needs over theoretical frameworks, employing quiet diplomacy and inclusive engagement with all conflict parties. The research identifies significant contrasts between practical and theoretical domains regarding ideological orientation, information access, implementation mechanisms, and success metrics for both quiet diplomacy and ASEAN's Five-Point Consensus. Limitations include reliance on policymakers' perspectives without equal representation from theoretical-domain viewpoints and information access restrictions under quiet diplomacy policy. The study illuminates how foreign policy practitioners translate theoretical concepts when navigating complex diplomatic situations, offering insights to strengthen foundations for more effective foreign policy by recognizing constraints and priorities between both theoretical and practical domains. Keywords: Theory-practice gap, Indonesia foreign policy, quiet diplomacy, Five-Point Consensus, Myanmar, ASEAN. Abstrak. Penelitian ini membahas kesenjangan antara teori dan praktik dalam kebijakan luar negeri Indonesia terhadap krisis Myanmar. Menggunakan metodologi kualitatif melalui wawancara dengan tiga informan dari Kementerian Luar Negeri Indonesia, penelitian ini menganalisis perspektif para pembuat kebijakan atas situasi di Myanmar. Temuan ini menunjukkan bahwa Indonesia mengadopsi pendekatan pragmatis yang memprioritaskan kebutuhan operasional di atas kerangka kerja teoritis, menggunakan diplomasi yang tenang dan keterlibatan inklusif dengan semua pihak yang berkonflik. Penelitian ini mengidentifikasi perbedaan yang signifikan antara ranah praktis dan teoretis mengenai orientasi ideologi, akses informasi, mekanisme implementasi, dan ukuran keberhasilan diplomasi damai dan Konsensus Lima Poin ASEAN. Keterbatasan yang ada termasuk ketergantungan pada perspektif pembuat kebijakan tanpa representasi yang setara dari sudut pandang domain teoritis dan pembatasan akses informasi dalam kebijakan diplomasi diam. Studi ini menjelaskan bagaimana praktisi kebijakan luar negeri menerjemahkan konsep-konsep teoretis ketika menghadapi situasi diplomatik yang kompleks, memberikan wawasan untuk memperkuat fondasi kebijakan luar negeri yang lebih efektif dengan mengenali kendala dan prioritas antara ranah teoretis dan praktis. Kata Kunci: Kesenjangan Teori-Praktik, Kebijakan luar negeri Indonesia, quiet diplomacy, Five-Point Consensus, Myanmar, ASEAN.